Technologically assisted intensive home treatment: feasibility study - Caspi, Asaf; Tzur Bitan, Dana; Halaly, Ofir; Hallaly, Ofri; Friedlander, Avraham; Barkai, Galia; Zimlichman, Eyal; Stein, Orit; Shani, Mordechai; Amitai, Ziv; Ansbacher, Tsofiya; Weiser, Mark (Frontiers in Psychiatry, 2023)
In recent year, many attempts have been made to provide patients with alternatives to psychiatric hospitalization during acute distress. Although several hospitalization alternatives have been offered, most of them still require patients to be distanced from their families, friends, and the social environment. In this report we describe the implementation of a novel approach to psychiatric care termed ‘Technologically assisted Intensive Home Treatment’, where patients arriving to emergency settings are directed to home care with technological aids that enable close monitoring and ongoing contact with their therapists. We describe the rationale and treatment principles of the treatment, and provide an elaborative description of the implementation process during the first year of implementation. Additional attention is given to factors associated with early dropout from the program, in order to inform readers of predictors to optimal care. Limitations and directions for future research and practice are discussed.